2001
DOI: 10.1046/j.1528-1157.2001.22200.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Slow Cortical Potentials in Patients with Refractory Epilepsy: A Controlled Outcome Study

Abstract: Summary:Purpose: To compare self-regulation of lowfrequency EEG components (slow cortical potentials, SCPs) with other methods of seizure control for patients with drugrefractory partial epilepsy and to separate the real anticonvulsive effect from placebo effects.Methods: Results of a treatment program of SCP selfregulation (experimental group) are compared with two groups of patients, one of which learned self-control of respiratory parameters (end-tidal CO 2 and respiration rate: RES group); the other receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
1
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(148 citation statements)
references
References 18 publications
3
136
1
8
Order By: Relevance
“…Therefore, during SCP training, patients were instructed to reduce negativity (i.e., to produce positive shifts) whenever they had the impression that they might have a seizure. Kotchoubey et al (2001) compared 35 sessions of SCP training with two control conditions: respiratory feedback (RESP) and changes in the medication (MED). There was no change in the RESP group, but both MED and SCP reduced significantly seizure frequency.…”
Section: Evidence Base Indications and Clinical Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, during SCP training, patients were instructed to reduce negativity (i.e., to produce positive shifts) whenever they had the impression that they might have a seizure. Kotchoubey et al (2001) compared 35 sessions of SCP training with two control conditions: respiratory feedback (RESP) and changes in the medication (MED). There was no change in the RESP group, but both MED and SCP reduced significantly seizure frequency.…”
Section: Evidence Base Indications and Clinical Experiencementioning
confidence: 99%
“…Similar to studies with frequency protocols there is no systematic research on this topic. Studies with SCP training have been performed with (e.g., Kotchoubey et al, 2001) or without (Heinrich et al, 2004;Rockstroh et al, 1993;Strehl et al, 2006) additional therapeutic elements. Unfortunately, a comparison between these two approaches cannot be performed as the effect of additional interventions cannot be isolated.…”
Section: Neurofeedback-and Else?mentioning
confidence: 99%
“…It has already been used as a therapeutic method in various mental illnesses, such as depression (Putman, 2002), attention-deficit/hyperactivity (Fuchs et al, 2003;Rossiter, 2004;Strehl et al, 2006;Kropotov et al, 2007), obsessive compulsive disorder (Hammond, 2003), epilepsy (Kotchoubey et al, 2001), anxiety and affective disorders (Hammond, 2005). Moreover, some studies have confirmed its efficiency in weakening the neuropsychological traits of substance and alcohol dependence (Saxby and Peniston, 1995;Masterpasqua and Healey, 2003;Scott et al, 2005;Sokhadze et al, 2008).…”
Section: Future Outlookmentioning
confidence: 99%
“…The placement of the electrodes and the channel names are seen in Figure 1. The EEG is used in several areas such as providing the interaction between human and machine [3,4], determining the response of the brain to the visual and auditory signals [5,6], allowing the diagnosis of psycho-physiological and neurological disorders [7][8][9][10][11], and helping doctors to make a quick assessment of normal and abnormal patterns using the peaks and valleys on the EEG for all age groups. Seizure disorders (such as epilepsy), a head injury, encephalitis, a brain tumour, encephalopathy, memory problems, sleep disorders, stroke, dementia, and etc.…”
Section: Introductionmentioning
confidence: 99%
“…The SCP has been correlated with a large number of cognitive processes in a systematic and topographically ways and has been determinately utilized in psychophysiological experiments to dissociate cognitive functions and motor performance of the brain [14,15]. Ergenoglu et al worked on determining the relationship between SCP and P300 amplitude [12], Khader et al analysed the relations between the SCP and Blood-oxygen-level dependent (BOLD) signal changes [16], Devrim et al investigated the detection of visual stimuli at sensory threshold using the SCP [6], Kotchoubey et al used the SCP training in the research on epilepsy with analysis of influencing factors [7,8]. Strehl et al used functional magnetic resonance imaging and the BOLD signal in the SCP to reduce epileptic seizure frequency [17], Siniatchkin et al evaluated the analysis of migraine [9], Schneider et al determined the efficiency of the SCP training in psychiatric patients with alcohol dependency [10], Cosch et al associated the SCP with the eventrelated potentials such as object, spatial, and verbal information [4], Hinterberger et al suggested a robust and steady communication method between computer and brain for amyotrophic lateral sclerosis patients using the SCP and studied on developing a tough translation device [3], Pham et al developed an auditory brain-computer stimuli for paralysed patients using the SCP [5].…”
Section: Introductionmentioning
confidence: 99%